Targeting immune-onco-metabolism for precision cancer therapy - Pajai, Sakshi; John, Jyoti E.; Tripathi, Satyendra Chandra (Frontiers in Oncology, 2023)
Immune cells play a key role in host defence against infection and cancer. Unlike infection, cancer is a multidimensional disease where cancer cells require continuous activation of certain pathways to sustain their growth and survival. The tumour milieu plays an important role in defining the metabolic reprogramming to support this growth and evasion from the immune system. Cancer and stromal cells modulate each other’s metabolism during cancer progression or regression. The mechanism related to change in the metabolism and its role in the crosstalk between tumour and immune cells is still an area of immense importance. Current treatment modalities can be immensely complemented and benefited by targeting the immuno-oncology metabolism, that can improve patient prognosis. This emerging aspect of immune-oncology metabolism is reviewed here, discussing therapeutic possibilities within various metabolic pathways and their effect on immune and cancer cell metabolism.